Suppression of neuronal apoptosis and glial activation with modulation of Nrf2/HO-1 and NF-kB signaling by curcumin in streptozotocin-induced diabetic spinal cord central neuropathy - Elsayed, Hassan Reda Hassan; Rabei, Mohammed R.; Elshaer, Mohamed Mahmoud Abdelraheem; El Nashar, Eman Mohamad; Alghamdi, Mansour Abdullah; Al-Qahtani, Zainah; Nabawy, Ahmed (Frontiers in Neuroanatomy, 2023)
Diabetes is a global disease, commonly complicated by neuropathy. The spinal cord reacts to diabetes by neuronal apoptosis, microglial activation, and astrocytosis, with a disturbance in neuronal and glial Nuclear factor erythroid 2-related factor/ Heme oxygenase-1 (Nrf2/HO-1) and Nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) signaling. Curcumin, a bioactive natural substance, showed neuroprotective role in many diseases. However, its role in the treatment of the diabetic central neuropathy of spinal cord and the underlying mechanisms still need clarification. The present study tried to evaluate the role of curcumin in diabetes-induced central neuropathy of the spinal cord in rats. Twenty rats were divided into three groups; group 1: a negative control group; group 2: received streptozotocin (STZ) to induce type I diabetes, and group 3: received STZ + Curcumin (150 mg/Kg/day) for eight weeks. The spinal cords were examined for histopathological changes, and immunohistochemical staining for Glia fibrillary acidic protein (GFAP); an astrocyte marker, Ionized calcium-binding adaptor molecule 1 (Iba1), a microglial marker, neuronal nuclear protein (NeuN); a neuronal marker, caspase-3; an apoptosis marker, Nrf2/HO-1, NF-kB, and oxidative stress markers were assessed. Curcumin could improve spinal cord changes, suppress the expression of Iba1, GFAP, caspase-3 and NF-kB, and could increase the expression of NeuN and restore the Nrf2/HO-1 signaling. Curcumin could suppress diabetic spinal cord central neuropathy, glial activation and neuronal apoptosis with the regulation of Nrf2/HO-1 and NF-kB signaling.